2008
DOI: 10.1016/j.molcel.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Hsp110:Hsc70 Nucleotide Exchange Machine

Abstract: Hsp70s mediate protein folding, translocation, and macromolecular complex remodeling reactions. Their activities are regulated by proteins that exchange ADP for ATP from the nucleotide-binding domain (NBD) of the Hsp70. These nucleotide exchange factors (NEFs) include the Hsp110s, which are themselves members of the Hsp70 family. We report the structure of an Hsp110:Hsc70 nucleotide exchange complex. The complex is characterized by extensive protein:protein interactions and symmetric bridging interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
261
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(284 citation statements)
references
References 42 publications
(64 reference statements)
17
261
1
Order By: Relevance
“…S1). This agrees well with previous studies that have shown Hsc70 bound to the free triskelia (14,15,22) and supports the idea previously proposed that Hsc70 acts to chaperone the released clathrin triskelia back to the plasma membrane (25), preventing formation of empty cages within the cell. It should be noted that, in a similar previous study, Schuermann et al (22) also observed a second, slower linear phase of disassembly following the initial fast exponential phase.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…S1). This agrees well with previous studies that have shown Hsc70 bound to the free triskelia (14,15,22) and supports the idea previously proposed that Hsc70 acts to chaperone the released clathrin triskelia back to the plasma membrane (25), preventing formation of empty cages within the cell. It should be noted that, in a similar previous study, Schuermann et al (22) also observed a second, slower linear phase of disassembly following the initial fast exponential phase.…”
Section: Discussionsupporting
confidence: 93%
“…Using a simple perpendicular light-scattering assay we have measured the in vitro disassembly of clathrin cages by Hsc70 and auxilin, which occurs rapidly with a t 1∕2 of approximately 10 s. This is comparable to recent results from experiments that used dynamic light scattering to monitor clathrin cage disassembly (21,22) but faster than earlier centrifugation-based studies that had t 1∕2 values ranging from 2-10 min (19,20,24) but that also contained adaptor proteins such as AP180 or AP2, which are known to stabilize the cages and may consequently have slowed down disassembly. In this study, we have increased the time resolution beyond that of dynamic light scattering by monitoring perpendicular light scattering, and analysis of these data has allowed us to isolate and describe individual steps in the chaperone-mediated disassembly of cages that hitherto have remained invisible.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous RDC analysis demonstrated that in solution the ADP-bound NBD exists in the "closed" conformation (10). X-ray structures of Hsp70 NBDs bound to their respective NEFs (12)(13)(14)(15)24), which enhance the rate of nucleotide release and binding, show subdomain IIB to be rotated about 10 to 30°with respect to the rest of the NBD and thus opening of the nucleotide-binding cleft ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Some insight into the nature of the conformational landscape of Hsp70 NBDs comes from X-ray structures of their complexes with nucleotide exchange factors (NEFs), which show an opening of the nucleotide-binding pocket relative to other NBD structures conformation (12)(13)(14)(15). Additionally, the recently determined X-ray structure of ATP-bound yeast Hsp110, Sse1, a distant relative of the Hsp70s, emerges as a plausible model for the Hsp70 ATP-bound conformation.…”
mentioning
confidence: 99%